Time’s Deadly Arrow: Time and Temporality in Narratives of Immaterial Labor - Sabine von Dirke (Studies in 20th & 21st Century Literature, 2016)
The article investigates the discourse on time and temporality in non-fictional and fictional accounts of paid, white collar labor, or, in the broader terminology of Maurizio Lazzarato, immaterial labor since the last quarter of the twentieth century. More specifically, it brings the critique of neoliberal capitalism by two influential social philosophers, Richard Sennett and Oskar Negt, in dialogue with fictional narratives of white collar labor: Rainer Merkel’s novel, Das Jahr der Wunder (The Year of Miracles, 2001), W.E. Richartz’s Büroroman (Office Novel, 1976) and Wilhelm Genazino’s Abschaffel-trilogy (1977-1979). Sennett and Negt’s non-fictional accounts contrast living and working conditions under the current hyper-flexible, neoliberal market economy to an earlier mode of a socially responsible capitalism. The latter is often nostalgically depicted as a golden age of a state-regulated labor market designed to protect the majority of the working population from exploitation and economic hardship. Yet, narratives on the working world published during the 1970s call into question the assumption that state-regulated work hours offer better conditions for lived time and the constitution of subjecthood.
Keywords: immaterial labor; German fiction; non-fictional accounts; time; temporality